The kind building - Tenorio, Gabriela de Souza (2022)
This paper introduces the concepts of the kind building – the one that would represent an architecture that seeks to favor public life and improve the pedestrian experience as they move around the city – and the hostile building, its antithesis. In Brazilian cities – and most likely in cities all around the world – many building additions, in new areas or in urban renewal processes, have very little, if any, concern to the public realm, bringing opacities and barriers to the streets. The kind building aims to outline a horizon for new architectural production, in a scenario of loss of urban vitality. It seeks to overcome the limitations imposed by occupation parameters, poor urban design, program constraints, and some client desires, as it’s architecture stems from choices based on a repertoire of spatial patterns that favor public life around it. This work treats architecture as an independent variable and focuses on the interface, one of the three levels of analysis encompassing studies on the configuration of public spaces and their relationship to the presence or absence of people. The interface level concerns the impact building frontages and components (access doors, public/private delimitation features, activities, windows) have on public life. The literature review helps define interface and boundary, discusses main concerns on public/private relationships, such as delimitation and alignment, setbacks, openings and activities, and brings studies on building-street interface in order to address its spatial qualities that influence pedestrian flow and encounter possibilities. From there, this paper presents, discusses, and illustrates the eight qualities of the kind building, showing that those qualities are not bounded to a certain kind of land use: i) be at ground level; ii) align with the public space, configuring it and turning their faces towards it; iii) invite and welcome pedestrians and cyclists before the car; iv) open doors to public spaces; v) open windows to public spaces; vi) do not use opaque elements as secondary boundaries; vii) do not use features to drive people away; and viii) do not place on their façade materials or objects that might worsen the external microclimate. Finally, it concludes that naming a phenomenon is a good start to raising awareness.